Authority of Surabaya City Government regarding Amending Fund Budget of Village - Yuliana, Fitri; Sesung, Rusdianto (PT. Riset Press International, 2024)
The village is part of the Sub-district formed by Regency / City Regional Regulation led by a head called Head of Village as a Sub-district apparatus responsible to the District Head. The Head of Village is appointed by the Regent/Mayor on the proposal of the Regional Secretary and Civil Servants who meet the requirements by the provisions of the Laws and Regulations which assist the duties of the Sub-District Head in carrying out village government activities, carrying out community empowerment, implementing community services, maintaining public peace and order, and so on. The limits of the Surabaya City Government's authority in making changes to the Fund Budget of Village must be by Government Regulation Number 17 of 2018 Article 30 where changes to the Fund Budget of Village are not less than 5% of the Regional Revenue and Expenditure Budget after deducting the Special Allocation Fund. In addition, the determination and management of the Fund Budget of Village must be transparent, including when the Surabaya City Government makes changes, they must still be based on Government Regulation Number 17 of 2018 and Law Number 1 of 2022, wherein Law Number 1 of 2022 Article 173a states that the Government can require Regions to prioritize the use of budget allocations for specific activities (refocusing), changes in allocations, and changes in the use of the APBD, and the Government can adjust the maximum amount of the APBD deficit and Regional Debt Financing. Legal conformity in managing the Fund Budget of the Village has been stated in Law Number 23 of 2014, Article 1, Paragraph 47, and Law Number 130 of 2018, Article 1, Paragraph 8. Other legal conformity in managing the Fund Budget of Village is also stated in Government Regulation Number 17 of 2018 Article 30, Paragraphs 6 and 7, and in Law Number 1 of 2022 Article 1, Paragraph 75.